Reducing meat consumption: Results from a German survey on attitudes, behaviour and willingness to change among adults - Almut Richter; Julia Wagner; Ramona Moosburger; Gert B. M. Mensink; Julika Loss (PLoS ONE, 2025)
Background Individual meat consumption in Germany has fallen slightly in recent years, but still exceeds the recommended quantities. High meat consumption has negative impacts both on human health and the environment. This study intends to identify which population groups in Germany may have already reduced their meat consumption, based on which motives, and to capture the willingness to limit future consumption. Methods Analyses are based on representative data from 3,178 adults living in Germany, collected in a cross-sectional, standardized telephone survey (German Health Update) in 2022. Differences between population groups are identified using chi-squared tests and logistic regression models. Results are presented with 95% confidence limits. Results 72% of the population intentionally avoid meat consumption at least occasionally. About half of the population intends to eat less meat in the future or already never eat meat. 23% have no current or future intention to limit their meat consumption. Women and higher educated persons more often claim to intentionally avoid meat consumption, currently and for the future. Those who currently eat meat less often are more likely to intend further reduction compared to those who eat meat frequently. The predominant motive for reducing meat consumption is “health” followed by “climate and environmental protection” and “animal welfare”. Climate protection as a motive for reducing meat consumption is more often mentioned by young persons and women, whereas health benefits are more important for persons aged 65 years and older. Conclusion A large proportion of the population already cuts down on meat consumption, at least occasionally. On the other hand, consumption levels in Germany are still very high. Climate and environment protection already play an important role for meat reduction, and may help leverage the transition to a more plant-based and healthier diet in the population.